(untitled) (The Pretoria Student Law Review, 2021)
The issue of land reform lies at the heart of African pride and dignity. However, colonisation leads to the systematic deprivation of land among the conquered people, as Ramose calls them. Ramose states that colonisation and racism were a dehumanising product of an unjust system, land deprivation being a sub-product of that system.1 Ramose calls it a double injustice in an unjust war. A system of injustice where the conquered was denied the basic courtesy of humanity by the conqueror. Apartheid and colonisation were the draconian systems that denied an entire people the ability to be regarded as an equal. However, the most tragic legacy left by apartheid and colonisation is the denying of conquered people their unique way of life and culture which is intertwined and dependant on land. The focus of this article is ascertaining what an African perspective to justice is and why it is needed as the primary premise in resolving land reform matters. Most importantly I will be looking at case law to assess whether South African courts are starting to turn to an African perspective to justice when dealing specifically with land wars in post-apartheid South Africa. I will also emphasise the need for our judicial system to re-imagine land and reform outside from what it is ordinarily understood to be in European norms.